Strategi Pemasaran UMKM Percetakan (Studi Kasus Ahmal Percetakan) - Sahwi Sahwi; Yuni Firayanti; Marhamah Marhamah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
Marketing strategy plays a very important role in marketing activities, the purpose of this research is to find out the marketing, strategy carried out by Ahmal Printing. The method used in this research is qualitive research with a descriptive approach, the informants in this reseach are four owners of Ahmal printing employees and two consumers of Ahmal Printing. The collection technique uses observation, interviews, and documentation, and to find out the factors that influence the marketing strategy at Ahmal Printing in increasing consumer loyalty. The theory used is a 4p mix, namely product, price, place, promotion and consumer loyalty. The results of the study show that Ahmal Printing’s marketing strategy uses digital marketing such as Instagram, Facebook, Tiktok and other media statuses with the aim of communicating a product to the puclic, sales promotions are quite effective, Ahmal Printing’s strategy introduces its products with paid advertising, iscarried out to attract consumers, instagram reels are used to maximize promotions, good product quality so that it can attact consumer interest, good product quality can attract consumers, factors that make Ahmal Printing have loyal consumers are because of the goog and friendly service to consumers, quality, and prices ranging from Rp. 1.200 to Rp 1.500 pcs for various products at Ahmal Printing depending on the design and product model according to consumer desires at a fairly affordable price so that consumers want to make repeat purchases at Ahmal Printing.